Timeline Original Motion Picture Soundtrack - Tyler, Brian (Varèse Sarabande, 2003)
Brian Tyler's big, bold and unabashedly old-fashioned (with modern splashes), Timeline is the definitive action score of 2003 and one of the best assembled albums of the year ... Timeline might be Brian Tyler's biggest break to date. And the results show a composer determined to deliver, not just go through the motions. The detail and drive in the action scoring and the sheer number of themes (rare in action pictures these days) translate well to CD. [www.cinemusic.net]
Keywords: CD